Abstract Legal Effect of Juridical Acts in European and Serbian Law - Dudaš, Atila (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
In this paper the author gives an overview of the development from abstract to causal juridical acts and explains the abstract legal effect of juridical acts in present-day European civil law (in the law of Germany, Austria, Switzerland and France). He concludes that in contemporary law juridical acts cannot have full abstract legal effect, as in archaic legal orders, because modern legal orders do not allow the creation of claims and debts in a way that entirely excludes the possibility to scrutinize whether a juridical act is null and void for the infringement of public order by its aim. In relation to the law of Serbia, the author refers to the difference between juridical acts that create obligations, that is claims and debts, and acts by which the parties merely dispose of the claims and debts already imposed. This division of juridical acts has its origins in the German legal culture, but it is fairly applicable to the Serbian law, as well. The author points out that the requirement of the Law on obligations, that all juridical acts must have a valid cause, applies without exception to juridical acts imposing an obligation (the so-called Verpflichtungsgeschäfte), regardless of whether they are concluded in the form of an abstract of causal act, i.e. whether the purpose of the transaction is determinable from their content. In this context he refers to the standpoint adopted in the doctrine that the cause of juridical acts gains relevance by three means: by the agreement of the parties, objection of the respondent and when the court determines ex officio whether the contract is contrary to public order. The author supports the point of view that in Serbian law juridical acts aimed merely to disposing of claims and debts already imposed (the so-called Verfügungsgeschäfte) may have a legal effect, which is independent from their cause. For these reasons, the author is of the opinion that in present-day legal orders, hence in Serbian law too, it is more appropriate to use the phrase “abstract legal effect of a juridical act”, which refers to a legal effect of an act, whereby the relevance of its cause is reduced or even eliminated, instead of the collocation “abstract juridical act”, which connotes a specific type of juridical act, one entirely independent from its cause.